Optimalisasi Energi Biomassa: Solusi Energi Terbarukan untuk Ekonomi Hijau dengan Tinjauan Finansial dan Lingkungan - Khairuna; Ulfia; Maryam; Samsul Ikhbar; Rahmi; Cut Rusmina (Jurnal Serambi Engineering, 2024)
The purpose of this article is to look into the optimisation of biomass energy as a strategic tool for establishing a green economy in Indonesia. Using a literature review technique, this study outlines a number of issues and solutions related with biomass energy production, as well as the possible financial and environmental benefits that can be realised. The problem analysis reveals that the key barriers to biomass energy growth are poor public awareness, limited infrastructure, and expensive beginning expenditures. To address these issues, the government must give appropriate financial and policy support, such as infrastructural assistance, subsidies, and tax breaks. This study is expected to result in a better understanding of the importance of biomass energy and the development of strategic steps to maximise its utilisation. Biomass energy can be a sustainable, environmentally friendly, and effective solution for overcoming the fundamental constraints and realising the present potential. The key recommendations of this article are the need for thorough education and campaigns to increase public knowledge and comprehension, as well as the importance of collaboration among government, industry, and society in the development of biomass energy. As a result, optimising biomass energy can help Indonesia shift to a more sustainable green economy.